Evaluation of microsatellite instability in routine examinations of surgical samples - Pawel Wlaszczuk; Aleksandra Kuzbinska; Zuzanna Dobrosz; Piotr Palen; Krzysztof Pawlicki (Wolters Kluwer Medknow Publications, 2022)
Context: Approximately 20%-30% of colon cancer cases have a hereditary basis. The genetic defect may involve mismatch repair (MMR) genes, which results in microsatellite instability (MSI). MMR-deficient colorectal cancer may occur due to germline mutation (Lynch syndrome) or be a sporadic one. A tumor's histological features, supported by a panel of immunohistochemistry stains, enables pathologists to assess the MMR status, which in turn has beneficial effects on clinical management. Aims: We aimed to show the relations between histopathological features identified during routine examinations and MMR genes' mutations. Methods and Material: We reviewed retrospectively the material of the Department of Pathology fulfilling the revised Bethesda Guidelines. Statistical Analysis Used: We used Chi-square test, Spearman test, and epidemiological analysis. Results: For the PMS2 gene, the positive predictive value (PPV) indicates that 91% of cases neither present any histological lesions nor have genetic abnormalities. The negative predictive value (NPV) indicates that only 50% of cases have both histological and genetic changes. For the MSH6 gene, the PPV indicates that 85% of tumors without specific histological features do not have genetic abnormalities. Conclusions: We advise universal staining for MLH1, MSH2, MSH6, and PMS2 in every newly diagnosed colon cancer, but due to costly analyses we suggest a protocol for the selection of cases for MMR examinations.